The relationship of company size, sales growth, and capital structure with firm value: Mediated by profitability - Savira, Nadya Pambudianing; Mahirun, Mahirun (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to analyze and obtain empirical evidence regarding the influence of profitability, company size, and sales growth on the value of companies mediated by capital structure. The population in this study is food & beverage companies listed on the Indonesia Stock Exchange in 2021-2023, with a sample of 49 companies and using the purposive sampling method. Quantitative data was collected and then processed using the Partial Least Square method. This study produced that size had a negative and insignificant effect on price to book value, sales growth had a significant positive effect on price to book value, debt to equity ratio had a positive and insignificant effect on price to book value, and return on assets had a significant positive effect on price to book value. Furthermore, sales growth has a non-significant positive effect on return on assets, debt to equity ratio has a significant negative effect on return on assets. In the test of the effect of mediation or indirect influence, the results were obtained that return on assets was not able to mediate the effect of sales growth and debt to equity ratio on price to book value.